Risk & return in regional development - Bonner, Emily E., author (Colorado State University. Libraries, 2006)
This dissertation is written in an attempt to expand the frontier of research in the sphere of risk and return associated with development and re-development issues facing regional economies. The premise of this study is to provide a "micro-foundations" view of the decisions facing the individual actors of local economies. Consequently, by analyzing the decisions faced at the micro level, this dissertation can provide public policy makers with varying insights into the mindset of private agents in a local economy. The result will be and increased understanding as to their role in addressing inefficiencies. In the absence of efficient diversification, in an effort to reduce the overall risk exposure of the economy, social planners expose their economy to an improper balance of risk and return, thus leading to greater inefficiency.
Risk and return in regional development
Keywords: finance; public policy; redevelopment; studies; research; censuses; trends; equilibrium; community; Brownfields; case studies; cooperation; adjustment; society; copyright; housing; conservation easements